The correlation between stable angina and inflammatory factors and blood lipids: a case-control study - Xiang, Lei (Frontiers in Cardiovascular Medicine, 2024)
Objective In this study, we aimed to compare the levels of inflammatory markers (C-reactive protein, CRP; procalcitonin, PCT) and blood lipids (total cholesterol, TC; triglyceride, TG; high-density lipoprotein cholesterol, HDL-C; low-density lipoprotein cholesterol, LDL-C) between patients with stable angina and control group, and to explore the correlation between these parameters and the severity and prognosis of stable angina. Methods We retrospectively selected 113 patients with stable angina and 128 control group from the medical record system, and compared their inflammatory factors and blood lipids. We also assessed the severity of angina using the Canadian Cardiovascular Society (CCS) classification and followed up the patients for 1 year to record any cardiovascular events. Results We found that patients with stable angina had significantly higher levels of CRP, TC, TG, and LDL-C, and lower levels of HDL-C than control group. Moreover, CRP, TC, TG, and LDL-C were positively correlated with the severity of angina, while HDL-C was negatively correlated. During the follow-up period, 37 patients with stable angina experienced cardiovascular events, and they had higher levels of CRP, TC, TG, and LDL-C, and lower levels of HDL-C than those who did not. Conclusion Our study suggests that inflammation and dyslipidemia are closely related to stable angina, and that inflammatory factors and blood lipids can be used as indicators of the severity and prognosis of stable angina.